Pre-operative Hypoglycemia in Patients Presenting for Surgery: A Hospital Based Crosssectional Study - Thapa, Ajay Singh; Yadav, Rajesh Kumar; Basnet, Rajan; Pradhan, Bijay; Maharjan, Rosee; Chaudhary, Samreta (Journal of Lumbini Medical College, 2021)
Introduction: Peri-operative glycemic control is an important factor for post-operative recovery and is well protocoled for diabetic patients in every setup. It is not always so with non-diabetic patients. This study aimed to observe the pre-operative glucose level and prevalence of hypoglycemia in patients presenting for surgery and its association with the duration of nil per oral period (NPO), age and intravenous fluids used in the pre-operative period. Methods: A cross-sectional study was conducted in the Department of Anesthesiology in a Nepalese medical college including all the patients posted for elective surgery over a period of three months. Socio-demographic and clinical details of the participants were collected in the operating theatre. Duration of NPO period and intravenous fluid prescribed in the pre-operative fasting period were recorded. A glucose strip test was performed in all the participants. Results: Participants were found to have fasted for an unnecessarily longer duration (12.84±2.27 hours). The incidence of hypoglycemia in patients posted for elective surgery was very high (43.3%). Ringer lactate and normal saline were equally prescribed (38.4%) and dextrose-normal saline was prescribed in the rest of the participants. Gender and type of intravenous fluids were positively correlated. NPO period was negatively correlated in overall participants. In hypoglycemic participants, we observed that lower glucose was influenced by pre-operative fluids, age and NPO duration. Conclusion: Pre-operative use of glucose containing fluids during NPO period is an important step to prevent hypoglycemia and related consequences.